Meningkatkan Hasil Belajar Pendidikan Agama Islam (PAI) Dengan Menggunakan Metode Diskusi di Kelas 5 SDN 18 Bonjol - Yulia Marlina, Desi (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to enhance student participation and learning outcomes in Islamic Religious Education (PAI) by using the discussion method in grade V of SDN 18 Bonjol. The research uses a Classroom Action Research (CAR) approach, conducted in two cycles. In the first cycle, although there was an improvement in learning outcomes, some students remained passive during discussions. In the second cycle, improvements were made by using visual media, more challenging questions, and reflection sessions. The evaluation results show that 100% of students achieved mastery, with a higher average score, and they were more active in the discussions. Based on these findings, it can be concluded that the discussion method is effective in increasing student involvement and their learning outcomes.